A Case Study of Drug Dependency (NSAIDs) in Shirshool (Headache) Healed Through Integrative Medicine (AYUSHDHARA, 2023)
Shira is the Uttamang i.e., most vital part of our body. Ayurveda is limited to pain and discomfort in Shira rather to brain disorders as such. Shirashool (headache) is the most common and frequently seen in day to day life due to the Stress, Vegdharan (to control forcefully natural functions like urine, faeces, cough or sneeze etc,) Ratrijagran (late night activity), Upvas (excessive control on appetite) Shoke (depressive thoughts), excessive work habits- the major root cause is excessive movement of Vata or overactive/imbalanced Vata Dosha. Jihva (tongue) examination is an important part of Ashtavidh pariksha mentioned in the text book of Yogratnakar. A tongue examination is typically conducted in conjunction with a thorough patient history. The vital organs of the body leave the imprint on the tongue surface- specific patterns or spots or colour. Tongue has its own language; it needs continuous practice. Examination of the tongue in Ayurveda is a easy valuable diagnostic tool that provides valuable and stored information about an individual's health and well-being or disease. Allopathic medicine like (NSAIDs) are most commonly used in headache as pain relieve medicine which has a lot of side effects; while holistic approach of Ayurveda is found to be very good results. Integrative therapy involves medicines, dietary schedule and yogic practices, shows sufficient significant changes in a patient. Mild recurrence which was seen in post follow up period was managed effectively through the yogic practices and proper guidance of counselling sessions on every Wednesday.